Experimental and Numerical Method for the Analysis of Warm Titanium Sheet Stamping of an Automotive Component. (29th April 2015) - Fiorentino, Antonio; Ceretti, Elisabetta; Giardini, Claudio
Abstract : Product design involves many aspects as geometry and material or mechanical requirements that have to be chosen on the base of the part requirements. Manufacturing process is the link between them representing a fundamental aspect of the product design process. Designers and technicians have a consolidated set of tools and knowledge based on long time experience, but the request of more new performing products characterized by more complex geometries or harder to form materials as Titanium alloys stimulated the use of numerical models. They allow us to study the product feasibility but they require reliable inputs for their development and validation. The present research focuses on sheet stamping processes and proposes a methodology that uses the Nakazima test to characterize the formability of the material and to develop and validate the model. In particular, the method is applied to cold (20°C) and warm (300°C) stamping of a complex automotive component made of CP Titanium. After characterizing the material and validating the model at the different temperatures, the stamping process is studied and results are compared. In particular, this approach allowed joining the experimental tests required to develop and validate the model, therefore reducing the resources required for the product design.